Gambaran Perilaku Perawatan Kaki Dan Faktor-Faktor Yang Mempengaruhi Perawatan Kaki Pada Penderita Diabetes Mellitus di Garut - Citra Windani Mambang Sari; Tina Lestari; Sandra Pebrianti (Jurnal Keperawatan Muhammadiyah, 2021)
Introduction: Foot care behavior is an important component in the prevention of diabetic feet, but most DM sufferees ignore this. Factors that influence the foot care behavior in people with diabetes mellitus, namely age, sex, education, knowledge, income and duration of diabetes. The purpose of this research was to determine the description of foot care behavior and the factors that influence foot care at Bayongbong Health Center. Method: This Research conducted using quantitative approach. The population in this research amounted to 35 respondents using total sampling technique. The instrument used was questionnaire which included: demographic data, health characteristics, knowledge and foot care behavior using the Nothingham Assessment of Functional Foot care (NAFF) questionnaire. Result: The result showed that most of the respondents had poor foot care behavior and almost half were in the vulnerable pre-elderly age 45-59 years with the sex of mostly women with an education level almost half elementary school, most of the income of respondents was > 1.8 M with the duration of suffering DM was mostly ≥ 3 years old and most respondents had good knowledge. Conclusion: From the result of the research, there needs to be education related to foot care that is more specific and more emphasized about the importance of good behavior in foot care, while the behaviors that need to be improved are foot hygiene, foot examination, footwear selection, prevention and management of injuries.